Multidecadal variability of potential temperature, salinity, and transport in the eastern subpolar North Atlantic. Issue 9 (4th September 2015) - Holliday, N. P.; Cunningham, S. A.; Johnson, C.; Gary, S. F.; Griffiths, C.; Read, J. F.; Sherwin, T.
Abstract The Extended Ellett Line (EEL) hydrographic section extends from Scotland to Iceland crossing the Rockall Trough, Hatton‐Rockall Basin, and Iceland Basin. With 61 full‐depth stations at a horizontal resolution of 10–50 km, the EEL samples the upper limb of the Atlantic Meridional Overturning Circulation flowing across the Iceland‐Scotland Ridge into the Nordic Seas. The Rockall Trough has been sampled nearly four times per year from 1975 to 1996, and the full section annually since 1996. The EEL is an exceptionally long‐time series of deep ocean temperatures and salinities. This study extends prior work in the Rockall Trough, and examines for the first time 18 year records in the Iceland and Hatton‐Rockall Basins. We quantify errors in the time series from two sources: observational errors and aliasing. The data quality and annual sampling are suitable for observing interannual to decadal variability because the variability exceeds our error estimates. The upper waters of all three basins are cooler/fresher from 1997 to 2001, warmer/more saline 2001–2006, and cooler/fresher from 2006 to 2014. A reference level for geostrophic shear is developed heuristically and by comparison with sea‐surface altimetry. The mean northward transport in the upper waters is 6.7 ± 3.7 Sv and there is a 6.1 ± 2.5 Sv southward flow below the thermocline. Although the magnitude of the Iceland Basin overturning circulation (4.3 ± 1.9 Sv) is greater than in the Rockall Trough (3.0 ± 3.7 Sv), the variability is greater in the Rockall Trough. We discuss the results in the context of our understanding of drivers of variability.